Double null points and magnetic reconnection - Galsgaard, K.; Rickard, G.J.; Reddy, R.V.; Nordlund, A. (My University, 1997)
2D reconnection is possible only in connection with the existence of a singularity in the magnetic field line topology, associated with a magnetic null point or a current sheet. Both of these provide an X-type structure of the magnetic field where fields of opposite polarity meet and reconnect. In 3D a similar topology is found in a null point pair, when the null points are connected by a separator line. The separator is defined as the intersection line of the two null-point fan planes. This paper reports on the topological evolution of this configuration with respect to different perturbations emerging from imposed boundary velocities, using a nonlinear numerical approach.
Keywords: Magnetic reconnection; Topology